Influencia fitosanitaria sobre la generación de alcaloides en cuatro genotipos de (Lupinus mutabilis) en la parroquia San Miguelito, cantón Píllaro, Tungurahua 2020. - Tacuri Ninacuri, Patricia Mariela (2021)
The present investigation Phytosanitary influences on alkaloids generation in four genotypes of (Lupinus mutabilis) at San Miguelito parish, Píllaro canton, Tungurahua 2020, having as objectives: to determine the alkaloid content in the four genotypes in their five harvest indices, to establish the relationship between alkaloid content and phytosanitary status of the crop, which it is carried out in two phases: field and laboratory. A DBCA design was carried out with three repetitions, net plots were delimited to determine the incidence of pests, diseases and pathophysiologies in the five harvest indices through a sampling of 5 plants from 5 central rows with a total of 25 plants. For laboratory phase evaluated factors were genetic materials, harvest indices, and health status. The analyzes were carried out at INIAP in the Nutrition Department. Important results were obtained from used indicators. For pest incidence indicator, it was determined that there are no significant differences. It was evidenced that is affected by pests, the presence of a low alkaloid percentage is noted, the genotype that obtained a low percentage is V4-Peruvian Local Ecotype, at index 5 (black), and plagued sanitary status with 1, 36%, while V1-450 Andino, in index 2 (lime green) and healthy health obtained status 6.83%. According to the Munsell Notation System in the sanitary state with plague they present greenish yellow colorations for values of <<hue>> it is found in the shade 2.5GY / 8, showing light colorations, while in the healthy state they present lime green colorations. for values of <<hue>> it is between 2.5GY / 10. Regarding chlorophyll, it indicates a low content in V3, index 3 (lime yellow), sanitary status plagued with 0.03% and the same variety in index 1 (green), healthy sanitary status with 0.17%. Differences were established in chlorophyll alkaloid content and color in four genotypes due to health status.